Effectiveness Of Using Liquid Smoke For Pest Control On Mustard Greens - Jayanti, Jayanti Agustina; Hartanti, Dyah Ayu Sri; Puspaningrum, Yessita (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Pest control in mustard greens cultivation is a crucial aspect of increasing agricultural productivity. This study aims to determine the effectiveness of liquid smoke as a natural pest control agent against pests such as the armyworm (Spodoptera litura), loopers (Plusia spp.), aphids (Aphidoidea), and grasshoppers (Caelifera). The research method used was observation of the presence of pests that appeared during the growth of mustard greens with various concentrations of liquid smoke applied to the plants. Observations were made on pest populations, plant damage, and plant growth throughout the study. The research data were analyzed qualitatively. The results showed that liquid smoke effectively reduced pest populations and the level of damage to mustard greens significantly. Higher concentrations of liquid smoke provided better results in pest control without negative effects on plant growth. The results of the 24-day study identified a total of 22 pest organisms on the control mustard green plants. The conclusion of this study is that liquid smoke is an effective and sustainable alternative for pest control in mustard greens. The use of liquid smoke can support safer and more sustainable agricultural practices